Pembangunan Minat Berkarier sebagai Auditor dengan Pengukuran Persepsi Mahasiswa terhadap Lingkungan Kerja Auditor Secara Global (Survei pada Mahasiswa Akuntansi Universitas Kristen Maranatha Bandung) - ., Rapina (Zenit, 2012)
Transformations and alterations are brought about by the Indonesian government, from practices related to accounting methods to the establishment of the professional body and the Public Accountant Compartment. A great number of cases happening to the profession of public accountants cause the decreasing trust of the public to the profession of an auditor. This research discusses how the influence of accounting student’s perception about the job atmosphere of an auditor to his job choice as an auditor. The influence of studen’ts perception can be judged from job duties and responsibilities; advancement training and superviso;, and personal concern. This research uses doubled linier regression  method to 50 respondents by using SPSS Pogram  17.0. The influence of accounting student’s  perception about the job  atmosphere of an auditor covers 36.6%, where the value has quite a big influence  over a job choice as an auditor and there is a strong relationship between the two variables, namely 67.2%. Keywords:  students perception about auditor, the job choice as an auditor,  job duties and responsibilities